Mental health status, life satisfaction, and mood state of elite athletes during the COVID-19 pandemic: A follow-up study in the phases of home confinement, reopening, and semi-lockdown condition - Mehrsafar, A. H.; Zadeh, A. M.; Gazerani, P.; Jaenes Sanchez, J. C.; Nejat, M.; Rajabian Tabesh, M.; Abolhasani, M. (Frontiers in Psychology, 2021)
Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by newly discovered Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). It was firstly reported in Wuhan, Hubei province (World Health Organization, 2020b), causing an unprecedented pandemic, forcing governments to impose an almost global quarantine (Spinelli and Pellino, 2020). The infection has spread rapidly around the world and COVID-19 has caused many severe and fatal medical cases (Rothan and Byrareddy, 2020). The escalating global morbidity and mortality of COVID-19 have raised significant public health concerns. At present, the focus of governments and the World Health Organization (WHO) is on controlling and mitigating the impact of this pandemic by identifying, testing, and treating infected people, and developing drugs, vaccines, and treatment protocols (Salathé et al., 2020). However, despite such efforts to defeat this pandemic, the directions where the pandemic will take in the coming days unknown. The global community is concerned about COVID-19 and its long-term consequences, such as the economy, industries, global market, human health, and health care. The COVID-19 outbreak also negatively influences various sports activities. In this regard, the 2020 Olympics and many national and international sport events/competitions have been postponed or canceled, and many organized training and team practices were limited. Consequently, many athletes faced tight restrictions to continue their regular training or activities. Health authorities recommend these limitations due to the nature of many team-based activities and crowd attendance that may facilitate a rapid spread of COVID-19, resulting in additional pressure on the health care system (World Health Organization, 2020a). In this regard, big sports events that resumed during the midst of the COVID-19 outbreak are now being referred to as huge "biological bombs" due to the spreading of the virus during these events (Gilat and Cole, 2020).